PENGARUH PROSES AGEING DAN POWDER COATING PADA ALUMINIUM PROFIL SECTION 7118 - Agris Setiawan; Ahmad Salman Taufiqi Firas (Journal of Metallurgical Engineering and Processing Technology, 2021)
The use of AA6063 aluminium alloy in profile form as a component for building construction is developing, along with the desire to reduce the weight of used components. However, the aluminium profile which came out of the extrusion machine doesn't have high mechanical properties, so the other processes are needed to increase aluminium profile's hardness. One of the processes which can increase its hardness is through a heat treatment process. Artificial ageing as heat treatment process was chosen, by using 185 °C temperature for 6 hours. Furthermore, aluminium profiles are also going through painting stages with powder coating. This internship report describes the effect of aging process on hardness of aluminium profiles and the effect of powder coating process on the thickness and weight of the aluminium profile section 7118. The result is, it was found that the aging process can increase the hardness of aluminium profile, from 3 wbs to 11 - 12 wbs. In other words, the mechanical properties of aluminium profiles have improved. Also, the powder coating process caused increase in thickness of aluminium profiles. From the analysis, it was found that in each part of the profile which was exposed to the paint is increasing in weight by 7.6%. However, the wrong coating process can cause aluminium profile to become overweight. This will cause significant losses for the company.